Transmethodology in social fascism times - Maldonado G., Efendy (2016)
These critical-reflexive notes seek to problematize the conjuncture in Latin America, from the analysis about the conservative onslaught in the last decade. During this period, the strategic rearrangements of media monopolies have designed efficient symbolic strategies of criminalization, restriction, espionage and discredit of the popular democratic strands in Latin America. The main objective is to contribute to the strengthening of critical thinking in communication. The arguments are constructed in dialogue with Sartre, Mattelart, Assange, Harnecker, Chomsky, Ianni, Eco, Verón, Ford, Toscani, Harvey, Clausewitz, Giap, Hobsbawm Gates Jr. and Marx. Critical investigations have confirmed the offensive of the neo-conservative media oligarchies in its intention to maintain the current power settingsof exclusion, authoritarianism and injustice.